2014
DOI: 10.1021/jp506555w
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacophore-Based Similarity Scoring for DOCK

Abstract: Pharmacophore modeling incorporates geometric and chemical features of known inhibitors and/or targeted binding sites to rationally identify and design new drug leads. In this study, we have encoded a three-dimensional pharmacophore matching similarity (FMS) scoring function into the structure-based design program DOCK. Validation and characterization of the method are presented through pose reproduction, crossdocking, and enrichment studies. When used alone, FMS scoring dramatically improves pose reproduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…Among several new scoring functions, a Boltzmann-weighted function is in development that employs multiple receptor conformations and / or homologs simultaneously. A pharmacophore matching scoring function has been developed [137] to account for hydrophobic, hydrogen bonding, charged, aromatic, and non-aromatic ring features in on-the-fly docking. And, a volume matching scoring function has been implemented that scores ligands based on their spatial overlap to a reference compound.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…Among several new scoring functions, a Boltzmann-weighted function is in development that employs multiple receptor conformations and / or homologs simultaneously. A pharmacophore matching scoring function has been developed [137] to account for hydrophobic, hydrogen bonding, charged, aromatic, and non-aromatic ring features in on-the-fly docking. And, a volume matching scoring function has been implemented that scores ligands based on their spatial overlap to a reference compound.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…Docking is also largely used for hit identification, representing the main example of receptor-based virtual screening (VS) procedure: a docking-based approach is commonly reported in several successful VS studies, both alone and in combination with other computational strategies [4][5][6][7][8] . For these reasons, the exponential attention that docking is gaining over time, as proved by the number of novel docking procedures and scoring functions reported in literature only in the last few years, cannot be blamed [9][10][11][12][13][14][15][16][17][18][19][20] . However, the remarkable interest for docking and for the development of new and optimized approaches is mainly due to the fact that the prediction of the actual binding mode of a ligand into a protein target is still far from being an easy task.…”
Section: Introductionmentioning
confidence: 99%
“…Among these strategies, the combination of different scoring functions (consenus scoring) to improve VS hit rates is a well known practice introduced by Charifson et al in 1999 31 that is still commonly applied [33][34][35][36][37][38] . A very recent approach concerns the introduction of a ligand-based component within the docking protocol that consists in exploiting the ligand information relative to crystallographic ligand-protein complexes for guiding pose selection and ranking, in a sort of combined ligand/receptor-based approach 12,[39][40][41] . Surprisingly, only very few studies evaluated the possibility of combining the results of different docking methods (consensus docking) to obtain reliable ligand binding poses and to improve the success rate in VS studies, as recently reported by Houston and Walkinshaw 42 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, pharmacophores have been applied as a post-processing step to docking when targeting VEGFR-2 [84] and hLTC4S [85]. The integration of pharmacophore similarity measures into DOCK [86] produced dramatic improvements in pose reproduction when measured over more than 1000 protein-ligand complexes [87].…”
Section: Using the Results Of Pharmacophore Searchmentioning
confidence: 99%